Sex Differences in the Association of HOMA-IR Index and BDNF in Han Chinese Patients With Chronic Schizophrenia - Yang, Yating; Zhang, Yulong; Wang, Juan; Ning, Xiaoshuai; Zhang, Yelei; Zhao, Tongtong; Zhong, Yi; Liu, Zhiwei; Xia, Lei; Li, Wenzheng; Yao, Xianhu; Zhang, Kai; et al. (Frontiers in Psychiatry, 2021)
Background: According to reports, there are significant gender differences in serum BDNF levels and metabolic indicators in patients with schizophrenia. Studies have found that BDNF is involved in blood sugar regulation. Homeostasis model assessment of insulin resistance (HOMA-IR) is currently a sensitive indicator for measuring insulin resistance. Our study aims to explore the gender difference in the relationship between serum BDNF levels and HOMA-IR in patients with chronic schizophrenia (CS). Methods: A total of 326 patients with CS were enrolled in this study. General information of all participants was collected. The Positive and Negative Syndrome Scale (PANSS) was used to assess mental symptoms and collect hematological indicators. The gender differences in serum BDNF levels, HOMA-IR index and other metabolic indexes were compared. Then, a linear regression analysis was performed on the relationship between the total HOMA-IR scores of male and female patients and BDNF. Results: The HOMA-IR index of female patients was significantly higher than that of males, but there was no significant difference in serum BDNF levels between male patients and female patients. There is a positive correlation between BDNF level and HOMA-IR index, and this relationship only exists in female patients. Conclusion: The results show that there are significant gender differences in HOMA-IR in patients with CS. In addition, only in female patients, there is a positive correlation between HOMA-IR index and BDNF level, which suggests that gender factors should be taken into account in evaluating the relationship between BDNF and blood glucose in patients with CS.